Sevoflurane Impairs Insulin Secretion and Tissue‐Specific Glucose Uptake In Vivo. Issue 6 (24th August 2018) - Høyer, Kasper F.; Nielsen, Thomas S.; Risis, Steve; Treebak, Jonas T.; Jessen, Niels
Abstract: The use of anaesthetics severely influences substrate metabolism. This poses challenges for patients in clinical settings and for the use of animals in diabetes research. Sevoflurane can affect regulation of glucose homoeostasis at several steps, but the tissue‐specific response remains to be determined. The aim of the study was to investigate the pharmacological effect of sevoflurane anaesthesia on glucose homoeostasis during hyperinsulinaemic clamp conditions, the gold standard method for assessment of whole‐body insulin sensitivity. Conscious mice (n = 6) and mice under sevoflurane anaesthesia (n = 8) underwent a hyperinsulinaemic clamp where constant infusion of insulin and donor blood was administered during variable glucose infusion to maintain isoglycaemia. 2‐[1‐ 14 C]‐deoxy‐D‐glucose was infused to determine tissue‐specific uptake of glucose in adipose tissue, heart, brain and skeletal muscle. Sevoflurane anaesthesia severely impaired insulin‐stimulated whole‐body glucose uptake demonstrated by a 50% lower glucose infusion rate (GIR). This was associated with decreased glucose uptake in brain, soleus, triceps and gastrocnemius muscles in sevoflurane‐anaesthetized mice compared to conscious mice. Plasma‐free fatty acids (FFA), a potent inducer of insulin resistance, increased by 42% in mice during sevoflurane anaesthesia. In addition, insulin secretion from pancreatic β‐cell was lower in fasted, anaesthetized mice. Sevoflurane anaesthesia impairs insulin secretion, induces insulin resistance in mice and reduces glucose uptake in non‐insulin‐sensitive tissue like the brain. The underlying mechanisms may involve sevoflurane‐induced mobilization of FFA.